Recent Advance of Nanomaterial-Mediated Tumor Therapies in the Past Five Years - Hao, Xinyan; Wu, Junyong; Xiang, DaXiong; Yang, Yongyu (Frontiers in Pharmacology, 2022)
Cancer has posed a major threat to human life and health with a rapidly increasing number of patients. The complexity and refractory of tumors have brought great challenges to tumor treatment. In recent years, nanomaterials and nanotechnology have attracted more attention and greatly improved the efficiency of tumor therapies and significantly prolonged the survival period, whether for traditional tumor treatment methods such as radiotherapy, or emerging methods, such as phototherapy and immunotherapy, sonodynamic therapy, chemodynamic therapy and RNA interference therapeutics. Various monotherapies have obtained positive results, while combination therapies are further proposed to prevent incomplete eradication and recurrence of tumors, strengthen tumor killing efficacy with minimal side effects. In view of the complementary promotion effects between different therapies, it is vital to utilize nanomaterials as the link between monotherapies to achieve synergistic performance. Further development of nanomaterials with efficient tumor-killing effect and better biosafety is more in line with the needs of clinical treatment. In a word, the development of nanomaterials provides a promising way for tumor treatment, and here we will review the emerging nanomaterials towards radiotherapy, phototherapy and immunotherapy, and summarized the developed nanocarriers applied for the tumor combination therapies in the past 5 years, besides, the advances of some other novel therapies such as sonodynamic therapy, chemodynamic therapy, and RNA interference therapeutics have also been mentioned.